Arenas vs. multifunctional stadia: which do spectators prefer? - Arne Feddersen; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2007)
Large sports stadia construction follows two different general concepts: (1) Mono-functional arenas which are specially suited for one sport exclusively and which are characterised by the absence of an athletic track. (2) Multifunctional sports stadia which can be used for different sporting or cultural events. Officials of clubs often argue that the atmosphere in an arena is significantly better than that of a multipurpose facility and that spectators prefer such an atmosphere. Estimated panel regressions with fixed effects show a significant positive effect of a mono-functional soccer stadium on spectator demand. Controlling for other demand determinants in the German professional soccer league, Bundesliga, an isolated effect of around 4,800 additional spectators a game can be found. This translates into a substantial increase of about 18.7% against the mean value of 25,602 spectators per Bundesliga game.
Keywords: L83; C23; C24; 330; Demand for sport; soccer; mono-functional arenas; multifunctional stadia